Determinants of Company Value: Study on Pharmaceutical Companies on the Indonesia Stock Exchange - Sambo, Eva Marin; Sufiati, Sufiati; Pura, Rahman (International Ecsis Association, 2023)
Company value is very important in investment transactions, and company management must understand the determinants to achieve company goals. The main operational goal of the company is to achieve the maximization of expected profits. Profit maximization is the company's only rational policy. This study aims to determine and examine the determinants of firm value: growth, firm size and financial performance. The research sample consisted of 9 pharmaceutical companies listed on the Indonesia Stock Exchange. Data is collected through financial statement documents for 4 years, 2018-2021. The number of data observed is 36 observational data. Data analysis used multiple regression analysis. The results showed that company growth and firm size positively and insignificantly affected firm value. Meanwhile, financial performance has a significant positive effect on firm value. The implications of the research results are theoretically as developing insight related to investment and portfolio management, then practically as information for investors in making investments.